Assessing the Use of BotulinumtoxinA for Hyperactive Urinary Tract Dysfunction a Decade After Approval: General Versus Local Anesthesia for BotulinumtoxinA Detrusor Injection - Heinrich Schulte-Baukloh; Apostolos Apostolidis; Catarina Weiss; Thorsten Schlomm; Sarah Weinberger; Dirk Höppner; Kathrin Haberecht; Carsten Waskow; Hendrik Borgmann; Jörg Neymeyer; Bernhard Ralla (Toxins)
Background: The onabotulinumtoxinA detrusor injection (OnabotA DI) was approved a decade ago for the treatment of patients with idiopathic overactive bladder (iOAB) or neurogenic detrusor overactivity (nDO) dysfunction who had not been treated successfully otherwise. The procedure is usually performed under local anesthesia (LA), and various approaches have been investigated to make the procedure as painless as possible. We examined the level of anxiety and pain experienced by patients who wanted to have the procedure performed under LA or general anesthesia (GA). Material and Methods: Patients scheduled for OnabotA DI were able to choose the anesthesia procedure (LA or GA). The Amsterdam Preoperative Anxiety and Information Scale (APAIS) was used to grade anxiety before anesthesia or before the procedure itself. Intra- and postoperative pain was determined using the Visual Analogue Scale (VAS). Various established questionnaires (including the Urinary Distress Inventory UDI-6), as well as a postoperative satisfaction questionnaire, were used to evaluate the success of the therapy. Results: In total, 104 patients (93 F, 11 M; age 64.0 (22–89) years; 80× iOAB, 24× nDO) were evaluated. OnabotA-DI was performed with LA in 72 patients and GA in 32. Stratified by first versus repeat injection in the LA group, there was a significant decrease in the Anxiety Score in the first vs. repeat injection group (p = 0.038). The LA group showed higher concerns in the anesthesia questions of the Amsterdam Preoperative Anxiety and Information Scale (APAIS) than the GA group (OR: 0.29, 95%CI: 0.02–1.74). The VAS Pain Score during the procedure was significantly lower in the GA group compared to the LA group (LA: 3.3 ± 2.2, GA group 1.5 ± 1.5; p < 0.001). There were no differences in the success of therapy. Despite the fear and pain, patients preferred LA to GA. Conclusions: This study shows that the anxiety and pain burden of patients undergoing OnabotA-DI under LA is significant in comparison to GA during the first injection, but insignificant for following injections. Overall, LA is favored over GA.